High-power low-loss NiCuZn microwave ferrite material and preparation method thereof

By combining NiCuZn ferrite powder and modified multi-walled carbon nanotubes, the material formulation was optimized, solving the problem of high loss in NiCuZn microwave ferrite materials, achieving high power and low loss, and improving electromagnetic performance.

CN119285346APending Publication Date: 2025-01-10NANJING BIAO ELECTRONIC TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411615442.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing NiCuZn microwave ferrite materials have high losses, making it difficult to meet the requirements of high-power applications.

Method used

High-power, low-loss microwave ferrite materials were prepared using NiCuZn ferrite powder and modified multi-walled carbon nanotubes. The material formulation was optimized by adding Bi2O3, MnCO3, and CaO, and the electromagnetic performance was improved by the π-π conjugation effect and conductivity of the modified multi-walled carbon nanotubes.

Benefits of technology

It significantly reduces material loss, improves electromagnetic performance, is suitable for high-frequency applications, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132081940000121
    Figure BDA0005132081940000121
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of microwave ferrite materials, in particular to a high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof.The high-power and low-loss NiCuZn microwave ferrite material is prepared from NiCuZn ferrite powder and modified multi-walled carbon nanotubes, Bi2O3 and CaO in additives in the NiCuZn ferrite powder can remarkably reduce the sintering temperature of ferrite, and the sintering temperature of the ferrite can be remarkably lowered; mnCO3 is added to improve the saturation magnetization intensity and electromagnetic performance of the ferrite material, in the sintering process, MnCO3 can inhibit generation of Fe < 2 + >, and the dielectric loss is increased along with the increase of Fe < 2 + >, so that the loss of the ferrite is reduced; the Pi-Pi conjugation effect formed by the modified multi-walled carbon nanotubes can improve the conductivity of the whole system, and the modified multi-walled carbon nanotubes are beneficial to loading ferrite and can enhance the conductivity and dispersion performance of the ferrite material, so that the electromagnetic performance of the ferrite material is improved, the loss is low, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave ferrite material preparation, and in particular to a high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof. Background Art

[0002] Ferrite is a special magnetic material, mainly composed of iron oxide and oxides of other metal elements, and belongs to non-metallic magnetic materials. According to the crystal structure, ferrite can be divided into three types: spinel type, garnet type and magnetoplumbite type. It exhibits high resistivity and good dielectric properties in electrical properties, because this property makes it possible to have lower losses in the high-frequency field. Although the saturation magnetization intensity of ferrites is almost less than half of that of magnetic alloys, they have the advantages of higher frequency of use, stronger corrosion resistance, lower price and higher heat resistance.

[0003] Microwave ferrite materials are the basic materials for manufacturing microwave devices including circulators and isolators. The working principle of microwave devices mainly utilizes the tensor characteristics of the material's magnetic permeability and the ferromagnetic resonance effect, so microwave ferrite materials and devices are also called gyromagnetic materials and devices. At present, such devices are widely used in various communication systems and radar systems, and the operating frequency also spans the L, S, C, X, K bands and millimeter wave bands. The miniaturization, low cost, easy batch production and good consistency of microwave gyromagnetic ferrite devices are the technical problems and development directions that need to be solved urgently for such devices.

[0004] Patent technology document CN101723657A discloses a method for preparing NiCuZn microwave ferrite material, firstly using analytically pure Fe2O3, NiO, ZnO and CuO as raw materials, weighing and mixing materials with a molar ratio of Ni:Cu:Zn:Fe=(1-x):y(xy):2; then ball milling, drying, pre-sintering at 900℃ for 2-4 hours; grinding again, adding 1-5% of low temperature sintering aid Bi2O3, ball milling again, drying, sintering at 900℃ for 4-6 hours, grinding to obtain the target product. The present invention adopts a solid phase process, optimizes the material formula and selects Bi2O3 as a sintering aid to obtain a NiCuZn microwave ferrite material with a spinel structure and adapted to the LTCC process. However, the microwave ferrite materials prepared by these existing preparation methods have high losses.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a high-power and low-loss NiCuZn microwave ferrite material. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof, so as to solve the problem of low power and high loss of microwave ferrite in the prior art.

[0007] Based on the above objectives, the present invention provides a high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof.

[0008] A high-power and low-loss NiCuZn microwave ferrite material is prepared from NiCuZn ferrite powder and modified multi-walled carbon nanotubes;

[0009] The NiCuZn ferrite powder is prepared from main materials and additives;

[0010] The main materials include Fe2O3, NiO, CuO and ZnO;

[0011] The additives include Bi2O3, MnCO3 and CaO;

[0012] The modified multi-walled carbon nanotube is prepared from multi-walled carbon nanotube, a strong oxidant, an aniline monomer and an initiator.

[0013] Preferably, the preparation process of the NiCuZn ferrite powder is as follows:

[0014] Step A1: Fe2O3, NiO, CuO and ZnO are mixed to obtain a main material, and the main material is mixed with anhydrous ethanol for a first ball milling to obtain a primary ball milling slurry;

[0015] Step A2: drying the first ball-milled slurry, passing it through a 40-70 mesh sieve, placing it in a sintering furnace, and pre-calcining it at 850-900° C. for 4-8 hours to obtain a pre-calcined powder;

[0016] Step A3: The pre-calcined powder is passed through a 40-70 mesh sieve to prepare a powder, an additive is added and mixed, and then mixed with anhydrous ethanol, ball-milled for a second time and then dried, and passed through a 40-70 mesh sieve to obtain NiCuZn ferrite powder.

[0017] Preferably, the mass ratio of Fe2O3, NiO, CuO, ZnO and anhydrous ethanol in step A1 is 68-70:8-10:15-18:22-25:45-50;

[0018] The time of the first ball milling in step A1 is 12-16 hours, and the rotation speed of the first ball milling is 200-280 rpm.

[0019] Preferably, in step A3, the mass ratio of the pre-burned powder, the additive, and the anhydrous ethanol is 85-90:8.5-12.5:48-52;

[0020] The additive in step A3 is a mixture of Bi2O3, MnCO3 and CaO in a mass ratio of 1-1.5:1-1.2:1.2-1.8;

[0021] The time of the second ball milling in step A3 is 5-8 hours, and the rotation speed of the second ball milling is 200-280 rpm.

[0022] Preferably, the preparation process of the modified multi-walled carbon nanotubes is as follows:

[0023] Step B1: Mix the multi-walled carbon nanotubes with a strong oxidant, perform ultrasound at 45-50° C. for 3-6 hours, dilute with water and filter, wash with anhydrous ethanol and water alternately until neutral, centrifuge, and dry at 85-90° C. for 8-12 hours under vacuum conditions to obtain carboxylated multi-walled carbon nanotubes;

[0024] Step B2: Disperse the carboxylated multi-walled carbon nanotubes and aniline monomers in a hydrochloric acid solution, place in a three-necked flask, stir at 0-5°C and 100-200rpm for 3-5h, add the initiator dropwise into the three-necked flask within 25-30min, react at 0-5°C for 5-7h, wash alternately with anhydrous ethanol and water until neutral, centrifuge, and freeze-dry to obtain modified multi-walled carbon nanotubes.

[0025] Preferably, the ratio of the multi-walled carbon nanotubes to the strong oxidant in step B1 is 12-15:20-25;

[0026] The strong oxidant is a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3.

[0027] Preferably, the usage ratio of the carboxylated multi-walled carbon nanotubes, aniline monomer, hydrochloric acid solution, and initiator in step B2 is 12-25 g: 2-3 g: 140-150 mL: 45-55 mL;

[0028] The concentration of the hydrochloric acid solution is 1-1.5 mol / L;

[0029] The initiator is prepared by mixing ammonium persulfate and hydrochloric acid solution in a dosage ratio of 3-3.5 g: 45-55 mL;

[0030] The concentration of the hydrochloric acid solution is 1-1.5 mol / L.

[0031] A method for preparing a high-power and low-loss NiCuZn microwave ferrite material, characterized in that it comprises the following steps:

[0032] Step C1: mixing NiCuZn ferrite powder and modified multi-walled carbon nanotubes, adding water for ball milling, drying, passing through a 40-70 mesh sieve, adding a binder for granulation, and obtaining granulated particles;

[0033] Step C2: Put the granulated particles into a mold for pressing, and then place them in a sintering furnace for sintering in air to obtain a high-power and low-loss NiCuZn microwave ferrite material.

[0034] Preferably, the mass ratio of the NiCuZn ferrite powder, the modified multi-walled carbon nanotubes, water and the binder in step C1 is 78-82: 3-9: 38-40: 52-58;

[0035] The adhesive is a 15-25wt% polyvinyl alcohol solution;

[0036] The ball milling time in step C1 is 2-4 hours, and the ball milling speed is 280-320 rpm.

[0037] Preferably, the pressing pressure in step C2 is 100-200 MPa, and the pressing time is 20-25 s;

[0038] In step C2, the sintering temperature is 1000-1500° C., and the sintering time is 3-5 hours.

[0039] Beneficial effects of the present invention:

[0040] The high-power and low-loss NiCuZn microwave ferrite material prepared by the present invention is prepared from NiCuZn ferrite powder and modified multi-walled carbon nanotubes. The Bi2O3 and CaO in the additives in the NiCuZn ferrite powder can significantly reduce the sintering temperature of the ferrite. An appropriate amount of Bi2O3 can increase the saturation magnetization intensity of the ferrite material and improve the electromagnetic performance. During the sintering process, the reduction reaction of MnCO3 can inhibit the Fe 2+ The dielectric loss increases with Fe 2+ MnCO3 will increase with the increase of , so the loss of ferrite will be reduced;

[0041] The modified multi-walled carbon nanotubes in the present invention are multi-walled carbon nanotubes modified with polyaniline formed by in-situ polymerization of carboxylated multi-walled carbon nanotubes and aniline monomers. The polyaniline has excellent electrical conductivity and dielectric properties. The polyaniline and the multi-walled carbon nanotubes are composited to form a π-π conjugated effect, which can improve the electrical conductivity of the entire system. At the same time, the modified multi-walled carbon nanotubes are conducive to loading ferrites, which can enhance their electrical conductivity and dispersion properties, thereby improving the electromagnetic properties of the ferrite material, thereby bringing about lower losses and having broad application prospects. DETAILED DESCRIPTION

[0042] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0043] The sources and properties of some of the raw materials used in the present invention are as follows:

[0044] Fe2O3 was purchased from Zhejiang Yamei Nanotechnology Co., Ltd., CAS: 1309-37-1; NiO was purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS: 1313-99-1; CuO was purchased from Wuhan Chujiang Haoyu Chemical Technology Development Co., Ltd., CAS: 1317-38-0; ZnO was purchased from Shandong Ruiqi Chemical Co., Ltd., CAS: 1314-13-2; Bi2O3 was purchased from Sichuan Liuzu Semiconductor Materials Co., Ltd., CAS: 1304-76-3; MnCO3 was purchased from Xi'an Qiyue Biotechnology Co., Ltd., CAS: 598-62-9; CaO was purchased from Ningbo Aikemu New Materials Co., Ltd., CAS: 1305-78-8; multi-walled carbon nanotubes were purchased from Xiamen Green Reagent Co., Ltd.; aniline was purchased from Aladdin Biochemical Technology Co., Ltd., CAS: 62-53-3.

[0045] Embodiment 1: A high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof, comprising the following steps:

[0046] S1: 68g Fe2O3, 8g NiO, 15g CuO and 22g ZnO were mixed to obtain a main material, and the main material was mixed with 45g anhydrous ethanol for the first ball milling to obtain a first ball milling slurry, wherein the first ball milling time was 12h and the first ball milling speed was 200rpm;

[0047] S2: drying the first ball-milled slurry, passing it through a 40-mesh sieve, placing it in a sintering furnace, and pre-calcining it at 850°C for 4 hours to obtain a pre-calcined powder;

[0048] S3: 85g of the pre-calcined powder was passed through a 40-mesh sieve to prepare a powder, 8.5g of the additive was added and mixed, and then mixed with 48g of anhydrous ethanol, and then ball-milled for the second time and dried, and passed through a 40-mesh sieve to obtain NiCuZn ferrite powder, wherein the additive was a mixture of 1gBi2O3, 1gMnCO3 and 1.2gCaO, and the second ball-milling time was 5h, and the second ball-milling speed was 200rpm;

[0049] S4: 12 g of multi-walled carbon nanotubes were mixed with 20 g of a strong oxidant, and the mixture was ultrasonically treated at 45°C for 3 h, and then diluted with water and filtered, and washed alternately with anhydrous ethanol and water until neutral, centrifuged, and dried at 85°C for 8 h under vacuum conditions to obtain carboxylated multi-walled carbon nanotubes. The strong oxidant was a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3;

[0050] S5: 12g of carboxylated multi-walled carbon nanotubes and 2g of aniline monomers were dispersed in 140mL of 1mol / L hydrochloric acid solution, placed in a three-necked flask, stirred at 0°C and 100rpm for 3h, 45mL of initiator was added dropwise to the three-necked flask within 25min, reacted at 0°C for 5h, washed alternately with anhydrous ethanol and water until neutral, centrifuged, and freeze-dried to obtain modified multi-walled carbon nanotubes, wherein the initiator was a mixture of 3g of ammonium persulfate and 45mL of 1mol / L hydrochloric acid solution;

[0051] S6: 78 g of NiCuZn ferrite powder and 3 g of modified multi-walled carbon nanotubes were mixed, 38 g of water was added for ball milling, dried, passed through a 40-mesh sieve, and 52 g of a binder was added for granulation to obtain granulated particles, wherein the binder was a 15 wt% polyvinyl alcohol solution;

[0052] S7: placing the granulated particles into a mold for pressing at a pressing pressure of 100 MPa for 20 seconds, sintering in air in a sintering furnace at a sintering temperature of 1000° C. for 3 hours, and obtaining a high-power and low-loss NiCuZn microwave ferrite material.

[0053] Embodiment 2: A high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof, comprising the following steps:

[0054] S1: 69g Fe2O3, 9g NiO, 16g CuO and 23g ZnO were mixed to obtain a main material, and the main material was mixed with 46g anhydrous ethanol for the first ball milling to obtain a first ball milling slurry, wherein the first ball milling time was 13h and the first ball milling speed was 220rpm;

[0055] S2: drying the first ball-milled slurry, passing it through a 50-mesh sieve, placing it in a sintering furnace, and pre-calcining it at 860°C for 5 hours to obtain a pre-calcined powder;

[0056] S3: 86g of the pre-calcined powder was passed through a 50-mesh sieve to prepare a powder, 9g of the additive was added and mixed, and then mixed with 49g of anhydrous ethanol, and then dried after a second ball milling, and passed through a 50-mesh sieve to obtain NiCuZn ferrite powder, wherein the additive was a mixture of 1.2gBi2O3, 1.1gMnCO3 and 1.4gCaO, and the second ball milling time was 6h, and the second ball milling speed was 240rpm;

[0057] S4: 13 g of multi-walled carbon nanotubes were mixed with 22 g of a strong oxidant, and the mixture was ultrasonically treated at 46 °C for 4 h, and then diluted with water and filtered, and washed alternately with anhydrous ethanol and water until neutral, centrifuged, and dried at 86 °C under vacuum conditions for 9 h to obtain carboxylated multi-walled carbon nanotubes. The strong oxidant was a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3;

[0058] S5: 14 g of carboxylated multi-walled carbon nanotubes and 2.5 g of aniline monomer were dispersed in 142 mL of 1.2 mol / L hydrochloric acid solution, placed in a three-necked flask, stirred at 1°C and 120 rpm for 4 h, 48 mL of initiator was added dropwise to the three-necked flask within 26 min, reacted at 2°C for 6 h, washed alternately with anhydrous ethanol and water until neutral, centrifuged, and freeze-dried to obtain modified multi-walled carbon nanotubes, wherein the initiator was a mixture of 3.2 g of ammonium persulfate and 46 mL of 1.2 mol / L hydrochloric acid solution;

[0059] S6: 79 g of NiCuZn ferrite powder and 4 g of modified multi-walled carbon nanotubes were mixed, 39 g of water was added for ball milling, dried, passed through a 50-mesh sieve, and 53 g of a binder was added for granulation to obtain granulated particles, wherein the binder was a 18 wt % polyvinyl alcohol solution;

[0060] S7: The granulated particles are placed into a mold for pressing at a pressing pressure of 120 MPa for 22 seconds, and sintered in air in a sintering furnace at a sintering temperature of 1200° C. for 4 hours to obtain a high-power and low-loss NiCuZn microwave ferrite material.

[0061] Embodiment 3: A high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof, comprising the following steps:

[0062] S1: 69.5 g Fe2O3, 9.5 g NiO, 17 g CuO and 24 g ZnO were mixed to obtain a main material, and the main material was mixed with 48 g anhydrous ethanol for the first ball milling to obtain a first ball milling slurry, wherein the first ball milling time was 15 h and the first ball milling speed was 260 rpm;

[0063] S2: drying the first ball-milled slurry, passing it through a 60-mesh sieve, placing it in a sintering furnace, and pre-calcining it at 890°C for 7h to obtain a pre-calcined powder;

[0064] S3: 88g of the pre-calcined powder was passed through a 60-mesh sieve to prepare a powder, 11g of the additive was added and mixed, and then mixed with 50g of anhydrous ethanol, and then dried after a second ball milling, and passed through a 60-mesh sieve to obtain NiCuZn ferrite powder, wherein the additive was a mixture of 1.4gBi2O3, 1.15gMnCO3 and 1.6gCaO, and the second ball milling time was 7h, and the second ball milling speed was 260rpm;

[0065] S4: 14 g of multi-walled carbon nanotubes were mixed with 24 g of a strong oxidant, and the mixture was ultrasonically treated at 48°C for 5 h, and then diluted with water and filtered, and washed alternately with anhydrous ethanol and water until neutral, centrifuged, and dried at 88°C under vacuum conditions for 11 h to obtain carboxylated multi-walled carbon nanotubes. The strong oxidant was a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3;

[0066] S5: 13g of carboxylated multi-walled carbon nanotubes and 2.8g of aniline monomer were dispersed in 148mL of 1.4mol / L hydrochloric acid solution, placed in a three-necked flask, stirred at 4°C and 180rpm for 4.5h, 52mL of initiator was added dropwise to the three-necked flask within 28min, reacted at 4°C for 6.5h, washed alternately with anhydrous ethanol and water until neutral, centrifuged, and freeze-dried to obtain modified multi-walled carbon nanotubes, wherein the initiator was a mixture of 3.4g of ammonium persulfate and 52mL of 1.4mol / L hydrochloric acid solution;

[0067] S6: 80 g of NiCuZn ferrite powder and 8 g of modified multi-walled carbon nanotubes were mixed, 39 g of water was added for ball milling, dried, passed through a 60-mesh sieve, and 56 g of a binder was added for granulation to obtain granulated particles, wherein the binder was a 20 wt% polyvinyl alcohol solution;

[0068] S7: The granulated particles are placed into a mold for pressing at a pressing pressure of 180 MPa for 24 seconds, and sintered in air in a sintering furnace at a sintering temperature of 1400° C. for 4.5 hours to obtain a high-power and low-loss NiCuZn microwave ferrite material.

[0069] Embodiment 4: A high-power and low-loss NiCuZn microwave ferrite material and a preparation method thereof, comprising the following steps:

[0070] S1: 70g Fe2O3, 10g NiO, 18g CuO and 25g ZnO were mixed to obtain a main material, and the main material was mixed with 50g anhydrous ethanol for the first ball milling to obtain a first ball milling slurry, wherein the first ball milling time was 16h and the first ball milling speed was 280rpm;

[0071] S2: drying the first ball-milled slurry, passing it through a 70-mesh sieve, placing it in a sintering furnace, and pre-calcining it at 900°C for 8 hours to obtain a pre-calcined powder;

[0072] S3: 90g of the pre-calcined powder was passed through a 70-mesh sieve to prepare a powder, 12.5g of the additive was added and mixed, and then mixed with 52g of anhydrous ethanol, and then dried after a second ball milling, and passed through a 70-mesh sieve to obtain NiCuZn ferrite powder, wherein the additive was a mixture of 1.5gBi2O3, 1.2gMnCO3 and 1.8gCaO, and the second ball milling time was 8h, and the second ball milling speed was 280rpm;

[0073] S4: 15 g of multi-walled carbon nanotubes were mixed with 25 g of a strong oxidant, and the mixture was ultrasonically treated at 50°C for 6 h, and then diluted with water and filtered, and washed alternately with anhydrous ethanol and water until neutral, centrifuged, and dried at 90°C for 12 h under vacuum conditions to obtain carboxylated multi-walled carbon nanotubes. The strong oxidant was a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3;

[0074] S5: 25g of carboxylated multi-walled carbon nanotubes and 3g of aniline monomers were dispersed in 150mL of 1.5mol / L hydrochloric acid solution, placed in a three-necked flask, stirred at 5°C and 200rpm for 5h, 55mL of initiator was added dropwise to the three-necked flask within 30min, reacted at 5°C for 7h, washed alternately with anhydrous ethanol and water until neutral, centrifuged, and freeze-dried to obtain modified multi-walled carbon nanotubes, wherein the initiator was a mixture of 3.5g of ammonium persulfate and 55mL of 1.5mol / L hydrochloric acid solution;

[0075] S6: 82g NiCuZn ferrite powder and 3-9g modified multi-walled carbon nanotubes are mixed, 40g water is added for ball milling, dried, passed through a 70-mesh sieve, and 58g of a binder is added for granulation to obtain granulated particles, wherein the binder is a 25wt% polyvinyl alcohol solution;

[0076] S7: placing the granulated particles into a mold for pressing at a pressing pressure of 200 MPa for 25 seconds, sintering in air in a sintering furnace at a sintering temperature of 1500° C. for 5 hours, and obtaining a high-power and low-loss NiCuZn microwave ferrite material.

[0077] Comparative Example 1:

[0078] Compared with Example 1, this comparative example does not add modified multi-walled carbon nanotubes during the preparation process of the high-power and low-loss NiCuZn microwave ferrite material. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a high-power and low-loss NiCuZn microwave ferrite material is obtained.

[0079] Comparative Example 2:

[0080] Compared with Example 1, this comparative example only replaces "modified multi-walled carbon nanotubes" with "multi-walled carbon nanotubes", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high-power and low-loss NiCuZn microwave ferrite material is obtained.

[0081] Comparative Example 3:

[0082] Compared with Example 1, this comparative example does not add additives during the preparation process of the high-power and low-loss NiCuZn microwave ferrite material, and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally a high-power and low-loss NiCuZn microwave ferrite material is obtained.

[0083] Comparative Example 4:

[0084] Compared with Example 1, this comparative example only replaces "3g modified multi-walled carbon nanotubes" with "50g modified multi-walled carbon nanotubes", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a high-power and low-loss NiCuZn microwave ferrite material is obtained.

[0085] Performance Testing:

[0086] Saturation magnetization test:

[0087] The high-power and low-loss NiCuZn microwave ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for saturation magnetization using a vibrating sample magnetometer (Nanjing Nanda Vanward Technology Co., Ltd., ND-VSM-903).

[0088] Ferromagnetic resonance linewidth test:

[0089] Referring to the IEC60556 test standard, the resonant cavity perturbation method was used to test the ferromagnetic resonance line width of the high-power, low-loss NiCuZn microwave ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5, and the working microwave fixed frequency was 9.3 GHz during the measurement. The ferrite sample needs to be processed before the test: Use an air compressor to put the sample into a grinder and blow it into a smooth small ball with a diameter of less than 1 mm.

[0090] Spin wave linewidth test:

[0091] The high-power and low-loss NiCuZn microwave ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to spin wave linewidth tests using a microwave resonant cavity (Shanghai Na Ai Experimental Instrument Co., Ltd., NAI-DMH).

[0092] Dielectric constant test:

[0093] The high-power and low-loss NiCuZn microwave ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for dielectric constant using a microwave resonant cavity (Shanghai Na Ai Experimental Instrument Co., Ltd., NAI-DMH) with a test frequency of 10 GHz.

[0094] Dielectric loss test:

[0095] The high-power and low-loss NiCuZn microwave ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to dielectric loss testing using a dielectric loss tester (Beijing Zhide Innovation Instruments and Equipment Co., Ltd., ZJD-B), with a test frequency of 10 GHz.

[0096] Table 1

[0097]

[0098] Data Analysis:

[0099] It can be seen from Table 1 that the high-power and low-loss NiCuZn microwave ferrite material prepared by the present invention has better electromagnetic properties and can achieve the purpose of high power and low loss; the high-power and low-loss NiCuZn microwave ferrite material prepared by the present invention is prepared from NiCuZn ferrite powder and modified multi-walled carbon nanotubes, and the Bi2O3 and CaO in the additives in the NiCuZn ferrite powder can significantly reduce the sintering temperature of the ferrite, and an appropriate amount of Bi2O3 can increase the saturation magnetization intensity of the ferrite material and improve the electromagnetic properties. During the sintering process, the reduction reaction of MnCO3 can inhibit the 2+ The dielectric loss increases with Fe 2+ The MnCO3 increases with the increase of MnCO3, so the loss of ferrite will be reduced; the modified multi-walled carbon nanotubes are formed by in-situ polymerization of carboxylated multi-walled carbon nanotubes and aniline monomers to form polyaniline-modified multi-walled carbon nanotubes, which have excellent electrical conductivity and dielectric properties. The polyaniline and multi-walled carbon nanotubes are composited to form a π-π conjugated effect, which can improve the electrical conductivity of the entire system. At the same time, the modified multi-walled carbon nanotubes are conducive to loading ferrites, which can enhance their electrical conductivity and dispersion properties, thereby improving the electromagnetic properties of ferrite materials, thereby bringing lower losses and having broad application prospects.

[0100] In Comparative Example 1, since modified multi-walled carbon nanotubes were not added during the preparation of the high-power and low-loss NiCuZn microwave ferrite material, it can be seen from Table 1 that the electromagnetic properties of the prepared ferrite material are reduced. This may be because the modified multi-walled carbon nanotubes have excellent electrical properties, good chemical stability and thermal stability, and the high conductivity of the modified multi-walled carbon nanotubes combined with the magnetism of the ferrite helps to adjust the dielectric constant and dielectric loss of the material, so that the ferrite material has higher power and lower loss;

[0101] In Comparative Example 2, since only "modified multi-walled carbon nanotubes" are replaced by "multi-walled carbon nanotubes", it can be seen from Table 1 that the electromagnetic properties of the prepared ferrite material are reduced. This may be because the modified multi-walled carbon nanotubes are formed by in-situ polymerization of carboxylated multi-walled carbon nanotubes and aniline monomers to form polyaniline-modified multi-walled carbon nanotubes. Polyaniline has excellent electrical conductivity and dielectric properties. The polyaniline and multi-walled carbon nanotubes are composited to form a π-π conjugated effect, which can improve the electrical conductivity of the entire system. At the same time, the special surface effect of the modified multi-walled carbon nanotubes is conducive to the modification and loading of ferrite metal particles, which can enhance its electrical conductivity and dispersion performance. If only multi-walled carbon nanotubes are used to composite the ferrite material, it is easy to cause agglomeration, which makes the dispersibility of the ferrite material poor, thereby causing the electromagnetic properties of the ferrite material to decrease;

[0102] Comparative Example 3 Since no additives were added during the preparation of the high-power and low-loss NiCuZn microwave ferrite material, it can be seen from Table 1 that the electromagnetic properties of the prepared ferrite material decreased. This may be because the Bi2O3 and CaO in the additives can significantly reduce the sintering temperature of the ferrite, which helps to save energy. An appropriate amount of Bi2O3 can increase the saturation magnetization intensity of the ferrite material and improve the electromagnetic properties. During the sintering process, MnCO3 is decomposed into MnO and MnO2 by heat. MnO2, Mn 4+ Mn 3+ , part of the oxygen is transferred to Fe 2+ , which can inhibit Fe 2+ The dielectric loss increases with Fe 2+ MnCO3 will increase with the increase of , so the loss of ferrite will be reduced;

[0103] In Comparative Example 4, since only "3g modified multi-walled carbon nanotubes" are replaced with "50g modified multi-walled carbon nanotubes", it can be seen from Table 1 that the electromagnetic properties of the prepared ferrite material are reduced. This may be because the modified multi-walled carbon nanotubes have excellent conductivity, and excessive use may reduce the electromagnetic properties of the ferrite. At the same time, excessive modified multi-walled carbon nanotubes are also prone to agglomeration, making the ferrite material uneven, which will also lead to a decrease in the electromagnetic properties of the ferrite material.

[0104] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0105] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-power, low-loss NiCuZn microwave ferrite material, characterized in that: Prepared from NiCuZn ferrite powder and modified multi-walled carbon nanotubes; The NiCuZn ferrite powder is prepared from main materials and additives; The main materials include Fe2O3, NiO, CuO and ZnO; The additives include Bi2O3, MnCO3 and CaO; The modified multi-walled carbon nanotube is prepared from multi-walled carbon nanotube, a strong oxidant, an aniline monomer and an initiator.

2. The high-power and low-loss NiCuZn microwave ferrite material according to claim 1, characterized in that: The preparation process of the NiCuZn ferrite powder is as follows: Step A1: Fe2O3, NiO, CuO and ZnO are mixed to obtain a main material, and the main material is mixed with anhydrous ethanol for a first ball milling to obtain a primary ball milling slurry; Step A2: drying the first ball-milled slurry, passing it through a 40-70 mesh sieve, placing it in a sintering furnace, and pre-calcining it at 850-900° C. for 4-8 hours to obtain a pre-calcined powder; Step A3: The pre-calcined powder is passed through a 40-70 mesh sieve to prepare a powder, an additive is added and mixed, and then mixed with anhydrous ethanol, ball-milled for a second time and then dried, and passed through a 40-70 mesh sieve to obtain NiCuZn ferrite powder.

3. The high-power and low-loss NiCuZn microwave ferrite material according to claim 2, characterized in that: The mass ratio of Fe2O3, NiO, CuO, ZnO and anhydrous ethanol in step A1 is 68-70:8-10:15-18:22-25:45-50; The time of the first ball milling in step A1 is 12-16 hours, and the rotation speed of the first ball milling is 200-280 rpm.

4. The high-power and low-loss NiCuZn microwave ferrite material according to claim 2, characterized in that: In step A3, the mass ratio of the pre-burned powder, the additive, and the anhydrous ethanol is 85-90:8.5-12.5:48-52; The additive in step A3 is a mixture of Bi2O3, MnCO3 and CaO in a mass ratio of 1-1.5:1-1.2:1.2-1.8; The time of the second ball milling in step A3 is 5-8 hours, and the rotation speed of the second ball milling is 200-280 rpm.

5. The high-power and low-loss NiCuZn microwave ferrite material according to claim 1, characterized in that: The preparation process of the modified multi-walled carbon nanotubes is as follows: Step B1: Mix the multi-walled carbon nanotubes with a strong oxidant, perform ultrasound at 45-50° C. for 3-6 hours, dilute with water and filter, wash with anhydrous ethanol and water alternately until neutral, centrifuge, and dry at 85-90° C. for 8-12 hours under vacuum conditions to obtain carboxylated multi-walled carbon nanotubes; Step B2: Disperse the carboxylated multi-walled carbon nanotubes and aniline monomers in a hydrochloric acid solution, place in a three-necked flask, stir at 0-5°C and 100-200rpm for 3-5h, add the initiator dropwise into the three-necked flask within 25-30min, react at 0-5°C for 5-7h, wash alternately with anhydrous ethanol and water until neutral, centrifuge, and freeze-dry to obtain modified multi-walled carbon nanotubes.

6. The high-power and low-loss NiCuZn microwave ferrite material according to claim 5, characterized in that: The ratio of the multi-walled carbon nanotubes to the strong oxidant in step B1 is 12-15:20-25; The strong oxidant is a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:

3.

7. The high-power and low-loss NiCuZn microwave ferrite material according to claim 5, characterized in that: The amount ratio of the carboxylated multi-walled carbon nanotubes, aniline monomer, hydrochloric acid solution, and initiator in step B2 is 12-25 g: 2-3 g: 140-150 mL: 45-55 mL; The concentration of the hydrochloric acid solution is 1-1.5 mol / L; The initiator is prepared by mixing ammonium persulfate and hydrochloric acid solution in a dosage ratio of 3-3.5 g: 45-55 mL; The concentration of the hydrochloric acid solution is 1-1.5 mol / L.

8. The method for preparing the high-power and low-loss NiCuZn microwave ferrite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step C1: mixing NiCuZn ferrite powder and modified multi-walled carbon nanotubes, adding water for ball milling, drying, passing through a 40-70 mesh sieve, adding a binder for granulation, and obtaining granulated particles; Step C2: Put the granulated particles into a mold for pressing, and then place them in a sintering furnace for sintering in air to obtain a high-power and low-loss NiCuZn microwave ferrite material.

9. The method for preparing the high-power and low-loss NiCuZn microwave ferrite material according to claim 8, characterized in that: The mass ratio of the NiCuZn ferrite powder, the modified multi-walled carbon nanotubes, water and the binder in step C1 is 78-82: 3-9: 38-40: 52-58; The adhesive is a 15-25wt% polyvinyl alcohol solution; The ball milling time in step C1 is 2-4 hours, and the ball milling speed is 280-320 rpm.

10. The method for preparing the high-power and low-loss NiCuZn microwave ferrite material according to claim 8, characterized in that: The pressing pressure in step C2 is 100-200 MPa, and the pressing time is 20-25 s; In step C2, the sintering temperature is 1000-1500° C., and the sintering time is 3-5 hours.

Citation Information

Patent Citations

  • Method for preparing NiCuZn microwave ferrite material

    CN101723657A

  • Preparation method of polyaniline / carbon nano tube compound electromagnetic shielding material

    CN102153862A

  • Ferrite-based ceramic composite material as well as preparation method and application thereof

    CN102390989A

  • Nickel-zinc ferrite material for wireless signal sensing, sheet core and preparation method thereof

    CN102807361A

  • Nickel-zinc ferrite-multiwalled carbon nanotube-epoxy resin composite and preparation method thereof as well as complex and preparation method thereof

    CN103435972A